2016
DOI: 10.1158/1940-6207.capr-15-0316
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Salivary Gland Adenoid Cystic Carcinoma

Abstract: Adenoid cystic carcinomas (ACCs) of the salivary glands are challenging to understand, treat, and cure. To better understand the genetic alterations underlying the pathogenesis of these tumors, we performed comprehensive genome analyses of 25 fresh-frozen tumors, including whole genome sequencing, expression and pathway analyses. In addition to the well-described MYB-NFIB fusion which was found in 11 tumors (44%), we observed five different rearrangements involving the NFIB transcription factor gene in seven t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 48 publications
5
77
0
Order By: Relevance
“…In addition to the PRKD2 rearrangement, the recurrent PAC RS3T also harboured a clonal NOTCH2 Q2409* truncating mutation and a MEF2B P315Qfs* frameshift mutation (Figure A; Table ). Mutations affecting genes of the Notch signalling pathway have been described in salivary gland cancers, particularly in adenoid cystic carcinoma . Consistent with the previously described paucity of gene CNAs in PACs, the gene copy number analysis performed here did not reveal complex patterns of CNAs or any recurrent CNA, despite the fact that all PACs analysed here were of high grade histologically (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…In addition to the PRKD2 rearrangement, the recurrent PAC RS3T also harboured a clonal NOTCH2 Q2409* truncating mutation and a MEF2B P315Qfs* frameshift mutation (Figure A; Table ). Mutations affecting genes of the Notch signalling pathway have been described in salivary gland cancers, particularly in adenoid cystic carcinoma . Consistent with the previously described paucity of gene CNAs in PACs, the gene copy number analysis performed here did not reveal complex patterns of CNAs or any recurrent CNA, despite the fact that all PACs analysed here were of high grade histologically (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…Of the 14 tumors with diffuse NICD1 positivity, we found that 11 harbored sequence variants within NOTCH1 mutational hotspots (exons 25-28, exon 34) that are predicted to produce NOTCH1 gain-of-function. The observed frequency of NOTCH1 mutations in ACCs from different patients that are diffusely positive for NICD1 (8 of 11 tumors, or 73%) is substantially higher than the frequency of NOTCH1 mutations that has been observed in NGS studies on unselected ACCs (711). By contrast, none of the 15 tumors with subset positivity for NICD1 had NOTCH1 mutations, a frequency significantly lower than that observed in ACCs with diffuse NICD1 positivity (p < 0.001, Fisher exact test).…”
Section: Resultsmentioning
confidence: 61%
“…The sets the stage for a second cleavage carried out by gamma-secretase, which allows the intracellular portion of Notch to translocate to the nucleus and turn on Notch target genes. Genes encoding Notch receptor and other components of the Notch pathway are recurrently mutated in many cancers, including ACC (711). We recently noted in a small series of primary ACCs and patient-derived xenograft (PDX) models that epithelial differentiation in ACC is associated with activation of NOTCH1 (1214), as assessed by immunohistochemical staining with a rabbit monoclonal antibody specific for a neoepitope located at the N-terminus of the NOTCH1 intracellular domain (NICD1) that is created when NOTCH1 is activated by gamma-secretase cleavage (15).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal translocations resulting in gene fusions and mutations in known cancer pathways appear to be of particular importance in several tumors of salivary origin. In adenoid cystic carcinoma, for example, the t(6;9) translocation resulting in the MYB-NFIB fusion product is well-described, and two recent next-generation sequencing studies found alterations in chromatin regulation and Notch signaling pathways(43, 44). The significance of the MECT1-MAML2 translocation and of TP53 mutation demonstrated here in MEC is therefore consistent with findings in other salivary tumors.…”
Section: Discussionmentioning
confidence: 99%